Educational video increases patients' knowledge regarding the lumbar puncture procedure: Results of a randomized controlled trial in clinical practice: Other innovative programs and practices. (7th December 2020) - Mofrad, Rosha Babapour; Fruijtier, Agnetha D; Visser, Leonie NC; Hoogland, Nina; Bouwman, Femke; Smets, Ellen; Teunissen, Charlotte E; van Der Flier, Wiesje
Abstract: Introduction: Patients' LP‐related anxiety was previously associated with a higher risk for post lumbar puncture (LP) complications. Since better understanding of the LP procedure might reduce anxiety, we developed an educational video explaining the LP procedure and potential complications. Here, we assessed the impact of the video on patients' LP‐related knowledge, anxiety, uncertainty, and post‐LP complications. Methods: Consecutive participants (n=148, n=94 underwent LP) who visited the Alzheimer center Amsterdam (table 1, data collection ongoing) were randomly assigned to one of three conditions: 1) home‐provision of the video (home‐viewers), 2) viewing the video in the clinic (clinic‐viewers), or 3) care as usual (controls). Questionnaires measured LP‐related knowledge (self‐developed), anxiety (STAI‐s) and uncertainty (MUIS) prior to (T0), at the start (T1) and end (T2) of participants' visit (figure 1). Post‐LP complications were reported via telephone‐consultation two weeks thereafter. The video was viewed after T0 and prior to T1. LP‐related knowledge, anxiety, uncertainty, and post‐LP complications were compared between conditions using either one‐way (LP‐ knowledge, post‐LP complications) or repeated measures ANOVA (anxiety, uncertainty) adjusted for age, sex and diagnosis. Since information processing can be affected in dementia patients, analyses were repeated in a subgroup (n=64) of non‐demented participants who underwent an LP. Results: Preliminary results show that viewing the video resulted in more LP‐related knowledge compared to controls at T1 ( F (2, 131)=14.0, p <0.001, η 2 p=0.18) and T2 ( F (2, 131), p =0.001, η 2 p=0.11; figure 2A). Anxiety levels decreased over time ( F (2, 248)=5.8, p =0.004, η 2 p=0.04) irrespective of condition (figure 2B). Within non‐demented participants who underwent an LP, knowledge was highest in clinic‐viewers compared to controls at T1 ( F (2, 58)=7.6, p =0.001, η 2 p=0.21), but not T2 ( F (2, 58)=0.73, p =0.49, η 2 p =0.03; figure 2C). In this subgroup, there was an interaction between condition and time ( F (4, 108), p =0.03, η 2 p=0.09): anxiety levels increased in controls in anticipation of their memory clinic visit, whereas this decreased in clinic‐viewers after viewing the video (figure 2D). Change in uncertainty ( F (4, 228)=1.8, p =0.13, η 2 p=0.03) or post‐LP complications ( F (2, 89)=0.58, p=0.56, η 2 p=0.01) did not differ between conditions. Discussion: Preparing patients for an LP through an educational video increased patients' knowledge about the LP procedure and its potential complications. The benefits of watching the educational LP‐video might even be greater for non‐demented subjects.